THE ROLE OF STEWARDS AT SPORTS EVENTS IN THE REPUBLIC OF SERBIA - Janković, Bojan D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The traditional view that only the police are responsible for security at sports events has largely been abandoned in the sense that stewards have more important place. This is also recognized in the Serbian legislation, in the standards of the Law on Private Security (LPS), the Law on the Prevention of Violence and Misconduct at Sports Events (LPVMSE), the Law on Public Assembly, and the international regulations of sports federations. The Council of Europe Convention on an Integrated Safety, Security and Service Approach at Football Matches and Other Sports Events – No. 218. (CETS 218), together with the Recommendation REC (2015) 1, and its annexes, which supersedes all previous recommendations, resolutions and statements, has also contributed to defining the role of stewards. Recommendation has become an integral part of the Convention (CETS 218). Common to all the aforementioned regulations is that the stewarding operations can be handled by persons who have completed special training. Unlike international regulations that provide extensive training for stewards, the existing programs in Serbia envisage very few hours of training. The work of stewards would certainly be aided by the improvement of certain legal regulations governing this area. The Republic of Serbia is not yet a signatory to the Convention (CETS 218), and it is necessary for the authorities to accede to its signing and ratification in order for Serbia to adopt the newly established European standards in this field as soon as possible.